Redox‐Enabled, pH‐Disabled Pyrazoline–Ferrocene INHIBIT Logic Gates. Issue 13 (6th June 2017) - Scerri, Glenn J.; Cini, Miriam; Schembri, Jonathan S.; da Costa, Paola F.; Johnson, Alex D.; Magri, David C.
Abstract: Pyrazoline‐ferrocene conjugates with an "electron‐donor–spacer–fluorophore–receptor" format are demonstrated as redox‐fluorescent two‐input INHIBIT logic gates. Abstract : Highs and lows : Pyrazoline‐ferrocene conjugates are demonstrated as redox‐fluorescent two‐input INHIBIT logic gates.